GPRKEY - A NOVEL GROUP KEY REKEYING TECHNIQUE FOR MANET - C Shanmuganathan; P Raviraj (ICTACT Journal on Communication Technology, 2018)
A Mobile Ad hoc Network (MANET) is a collection of autonomous nodes or mobile devices that can arrange themselves in various ways and work without strict network administration. Ensuring security in mobile ad hoc networks is a challenging issue and most of the applications in mobile ad hoc networks involve group oriented communication. Mostly cryptographic techniques are used to provide the security to MANETs. Cryptographic techniques will not be efficient security mechanism if the key management is weak. The issue of packet loss in MANET that is caused due to multi casting and backward and forward secrecy results in mobility. Hence, we investigate on this issue and propose a method to overcome this scenario. On analysing the situation we find that frequent rekeying leads to huge message overhead and hence increases energy utilization. With the existing key management techniques it causes frequent disconnections and mobility issues. Therefore, an efficient multi casting group key management will help to overcome the above problems. In this paper we propose a novel group key rekeying technique named GPRKEY (Group key with Periodic ReKEYing) deal with scalability issue of rekeying and also analyze the performance of the newly proposed key management method using key trees. In this approach we use the periodic rekeying to enhance the scalability and avoid out of sync problems. We use sub trees and combine them using the merging algorithm and periodic re-keying algorithm. The GPRKEY is evaluated through NS-2 simulation and compared with existing key management techniques OFT (One-way Function Tree) and LKH (Logical Key Hierarchy). The security and performance of rekeying protocols are analyzed through detailed study and simulation.